Menyoal Bagian Mutlak (Legitime Portie) Ahli Waris Dalam Warisan Menurut KUHPerdata - Muhammad, Aldi Pradana; Jatmikowati, Sri Wahyu (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to fully comprehend the essential parts of the inheritance assets that must be directly given to heirs according to legal provisions, where the deceased is not allowed to specify something for a particular part, either as a gift to the living or as a will, as regulated in Article 913 of the Civil Code. The author employs a type of normative juridical research, which focuses on the analysis of legal regulations, legal principles, relevant literature, expert opinions, and regulations related to the research topic.